METHODOLOGICAL SUPPORT OF TEACHING FUTURE EDUCATORS THE DESIGN OF AN INFORMATION EDUCATIONAL ENVIRONMENT IN THE PROCESS OF PROFESSIONAL PREPARATION - Kucher Svitlana (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article examines the relevant needs of methodological support for the training of future educators to design an information educational environment in the process of course planning (topics, modules, units, and educational sessions). The purpose of the article is to determine the specifics and main directions of methodological support for the professional training of future educators in the process of studying the course “Pedagogical Design” whose main task is to teach the design of a holistic information educational environment. The development of methodological support for the training of future educators to design an information educational environment required completing the following tasks: studying the state of readiness for designing an information educational environment by future educators, as well as practicing educators; analysis of the requirements for the information educational environment and the current state of the problem in practice; identifying the leading methodological aspects of work in a digital educational environment that is modern, accessible and personal-centred. In order to find out the contradictions and gaps in the methodological support of the educational environment, related to the specifics of distance learning with Moodle tools, a SWOT-analysis was used, in which both students of master’s degree level and teachers were involved. Using the methods of theoretical analysis and synthesis of scientific and pedagogical research, modern approaches to the formation of an information educational environment have been developed, in particular from the point of view of educational design, and there has been found out such an approach to design which is called “Backward Design” or “Understanding by Design”. On the basis of the framing approach of “Backward Design”, reference points are proposed for the development of methodical training support for the design of a holistic educational environment by future educators (determination of learning goals based on a person-centered approach; design of measurement of the goal as a planned result; planning of interactive experience of educational activities). The specificity of the methodological support for the design of a modern information educational environment is manifested in the fact that the traditional methods of preparing educational materials by the teacher are ineffective because they are based on the content of the textbook or curriculum, but not on the context which is built on the activity of those who study. This is especially relevant in the conditions of distance education. From the point of view of “Understanding by Design”, the educator develops a learning system that is effective and appropriate for the participants. It is assumed that the creation of educational content (learning content) within the limits of the whole subject or its separate part from the point of view of the taxonomy of understanding will allow personalizing the educational process to ensure deep knowledge upon completion. The development of the content of training courses built on the principles of Backward Design can give the educator new opportunities to enhance perceptivity to learning.